Peran Pemahaman Teori Ambiguitas dalam Menyelesaikan Kesalahpahaman dalam Berkomunikasi - Diani, Irma; Afrodita, Meli; Lazfihma, Lazfihma (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Ambiguity is prone to occur in conversation. When communicating, the possibility of misunderstandings occurs due to unclear intentions or the existence of double meanings in the words and sentences used. Misunderstanding when communicating can occur at the phonetic, grammatical and lexical levels. This research method uses a descriptive method with a qualitative approach. Data were obtained by interviewing and recording conversations of Bengkulu University students. Recorded data was obtained from 36 informants. Then the data is transcribed and then classified. After being classified, the data were analyzed using ambiguity theory. Finally, conclusions are drawn. In this study, the misunderstandings found in student conversations occurred at the grammatical and lexical level. An understanding of semantics, especially ambiguity theory, needs to be mastered by both educators and students in order to overcome and resolve misunderstandings in conversation.